Ionizing Radiation (IntechOpen, 2025)
This Edited Volume Ionizing Radiation - Insights into Chemistry, Biology, and Applications, is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of ionizing radiation. The book comprises single chapters authored by various researchers and edited by an expert active in the ionizing radiation research area. All chapters are complete in themselves but united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts by international authors and open new possible research paths for further novel developments.